Alkali Atoms Diffusion Mechanism in CuInSe2 Explained by Kinetic Monte Carlo Simulations. Issue 6 (16th April 2019) - Kormath Madam Raghupathy, Ramya; Kühne, Thomas D.; Henkelman, Graeme; Mirhosseini, Hossein
Abstract: Adaptive kinetic Monte Carlo simulation (aKMC) is employed to study the dynamics and the diffusion of point defects in the CuInSe2 lattice. The aKMC results show that lighter alkali atoms can diffuse into the CuInSe2 grains, whereas the diffusion of heavier alkali atoms is limited to the Cu‐poor region of the absorber. The key difference between the diffusion of lighter and heavier alkali elements is the energy barrier of the ion exchange between alkali interstitial atoms and Cu. For lighter alkali atoms like Na, the interstitial diffusion and the ion‐exchange mechanism have comparable energy barriers. Therefore, Na interstitial atoms can diffuse into the grains and replace Cu atoms in the CuInSe2 lattice. In contrast to Na, the ion‐exchange mechanism occurs spontaneously for heavier alkali atoms like Rb and the further diffusion of these atoms depends on the availability of Cu vacancies. The outdiffusion of alkali substitutional atoms from the grains results in the formation of Cu vacancies which in turn increases the hole concentration in the absorber. In this respect, Na is more efficient than Rb due to the higher concentration of Na substitutional defects in the CuInSe2 grains. Abstract : Adaptive kinetic Monte Carlo (aKMC) simulations are employed to study the diffusion of alkali atoms in the CuInSe2 lattice. The results show that the key difference between the diffusion of lighter alkali atoms and heavier alkali atoms is the energy barrier for the ion exchange between the interstitial alkali and Cu atoms.